1991
DOI: 10.1007/bf03347890
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism due to familial pituitary resistance to thyroid hormone: successful control with 3, 5, 3′ triiodothyroacetic associated to propranolol

Abstract: We herein describe a family with thyroid hormone resistance. Thyroid hormones and basal TSH were elevated. Pituitary tumor or abnormality in thyroid hormone binding proteins were ruled out by appropriate tests. Mother and sister of the propositus presented similar abnormal hormonal features but no hyperthyroidism. Initially the patient was treated with carbimazole (30 mg/day): three months later a dramatic increase in the size of the thyroid gland and in TSH levels (12.5 to 28 mU/l) were noted. Thereafter, dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a subgroup of RTHβ patients, TA 3 is able to decrease TSH and consequently the high serum T 4 and T 3 levels. Since the thyromimetic effects of TA 3 itself do not fully compensate the reduction in endogenous TH levels, it alleviates the thyrotoxic symptoms including tachycardia, goiter, excessive sweating and behavioral problems (BeckPeccoz et al 1983, Lind & Eber 1986, Faglia et al 1987, Salmela et al 1988, Kunitake et al 1989, Smallridge et al 1989, Beck-Peccoz et al 1990, Aguilar Diosdado et al 1991 Crino et al 1992, Dulgeroff et al 1992, Ueda et al 1996, Darendeliler & Basx 1997, Radetti et al 1997, CliftonBligh et al 1998, Persani et al 1998, Asteria et al 1999, Kong et al 2005, Torre et al 2005, Wu et al 2006, Gurgel et al 2008, Santos et al 2008, Guran et al 2009, Anzai et al 2012, Ferrara et al 2012, Ramos-Prol et al 2013, Stagi et al 2014, Chatzitomaris et al 2015, Xue et al 2015. However, some patients do not respond to TA 3 treatment, which is assumed to depend on the type or location of the mutation (Hamon et al 1988, Persani et al 1998.…”
Section: Rthβmentioning
confidence: 99%
“…In a subgroup of RTHβ patients, TA 3 is able to decrease TSH and consequently the high serum T 4 and T 3 levels. Since the thyromimetic effects of TA 3 itself do not fully compensate the reduction in endogenous TH levels, it alleviates the thyrotoxic symptoms including tachycardia, goiter, excessive sweating and behavioral problems (BeckPeccoz et al 1983, Lind & Eber 1986, Faglia et al 1987, Salmela et al 1988, Kunitake et al 1989, Smallridge et al 1989, Beck-Peccoz et al 1990, Aguilar Diosdado et al 1991 Crino et al 1992, Dulgeroff et al 1992, Ueda et al 1996, Darendeliler & Basx 1997, Radetti et al 1997, CliftonBligh et al 1998, Persani et al 1998, Asteria et al 1999, Kong et al 2005, Torre et al 2005, Wu et al 2006, Gurgel et al 2008, Santos et al 2008, Guran et al 2009, Anzai et al 2012, Ferrara et al 2012, Ramos-Prol et al 2013, Stagi et al 2014, Chatzitomaris et al 2015, Xue et al 2015. However, some patients do not respond to TA 3 treatment, which is assumed to depend on the type or location of the mutation (Hamon et al 1988, Persani et al 1998.…”
Section: Rthβmentioning
confidence: 99%
“…Clinically, 3,5,3 0 -triiodothyroacetic acid (TRIAC) was reported to be available for the management of thyrotoxicosis due to PRTH [18][19][20]. The molecular aspects revealed that TRIAC has a higher affinity for TRb1 than T3, whereas the two compounds show equivalent affinities for TRa1 [21,22].…”
Section: Therapeutic Approach and Optionsmentioning
confidence: 98%
“…The levothyroxine therapy should be conducted considering the clinical condition of these patients and imitating as much as possible the preoperative hormonal pattern for serum T 4 and T 3 even if optimal TSH suppression cannot be achieved (Paragliola et al 2011). Other drugs of interest which can suppress TSH secretion include triiodothyroacetic acid and dopamine agonists (Aguilar Diosdado et al 1991, Dulgeroff et al 1992.…”
Section: Treatmentmentioning
confidence: 99%